Radiotherapy - Onal, Cem (IntechOpen, 2017)
Radiotherapy plays a key role in the treatment of many cancer types. This book is intended to bring forward the recent advancements in the field of radiation oncology. It presents the experience of several researchers who dedicate many hours a day to not only treat patients but also assess the physical aspects of newer radiotherapy facilities. This book contains many valuable contributions from radiation oncology physicians and medical physicists who are experts in their fields.